Laboratory Investigation of the Hydrophobicity Transfer Mechanism on Composite Insulators Aged in Coastal Service - Mavrikakis, N.; Siderakis, K.; Koudoumas, E.; Drakakis, E.; Kymakis, E. (Engineering, Technology & Applied Science Research, 2016)
Silicone rubber (SIR) insulators are known to maintain their surface hydrophobicity even under severe pollution conditions in contrast to the other composite insulator materials used at the last decades. This critical advantage of silicone rubber insulators has made them dominant in high voltage power systems despite the fact that there are other composite materials with better static hydrophobicity. In service conditions, priority is given to the dynamic performance of hydrophobicity due to the unpredictable environmental pollution conditions. This dynamic performance of silicone rubber insulators is also known as hydrophobicity transfer mechanism. In literature, the hydrophobicity transfer mechanism of silicone rubber is related to the reorientation of methyl-groups and the existence of low molecular weight components. However there are many parameters which can change the effectiveness of this mechanism. Some of them referred to the ageing effects on the material structure. Thus it is of great importance to investigate the hydrophobicity transfer mechanism of field aged composite insulators. For this reason a new experimental procedure is introduced based on Cigre TB 442. The results of field aged insulators are compared to that of a new SIR insulator revealing the superiority of silicone rubber even after 17 years of field ageing.